Health economic evaluation of vaccination strategies for the prevention of herpes zoster and postherpetic neuralgia in Germany - Ultsch, Bernhard; Weidemann, Felix; Reinhold, Thomas; Siedler, Anette; Krause, Gérard; Wichmann, Ole (BMC health services research, 2013)
Background Herpes zoster (HZ) is a self-limiting painful skin rash affecting mostly individuals from 50 years of age. The main complication is postherpetic neuralgia (PHN), a long-lasting pain after rash has resolved. A HZ-vaccine has recently been licensed in Europe for individuals older than 50 years. To support an informed decision-making for a potential vaccination recommendation, we conducted a health economic evaluation to identify the most cost-effective vaccination strategy. Methods We developed a static Markov-cohort model, which compared a vaccine-scenario with no vaccination. The cohort entering the model was 50 years of age, vaccinated at age 60, and stayed over life-time in the model. Transition probabilities were based on HZ/PHN-epidemiology and demographic data from Germany, as well as vaccine efficacy (VE) data from clinical trials. Costs for vaccination and HZ/PHN-treatment (in Euros; 2010), as well as outcomes were discounted equally with 3% p.a. We accounted results from both, payer and societal perspective. We calculated benefit-cost-ratio (BCR), number-needed-to-vaccinate (NNV), and incremental cost-effectiveness ratios (ICERs) for costs per HZ-case avoided, per PHN-case avoided, and per quality-adjusted life-year (QALY) gained. Different target age-groups were compared to identify the most cost-effective vaccination strategy. Base-case-analysis as well as structural, descriptive-, and probabilistic-sensitivity-analyses (DSA, PSA) were performed. Results When vaccinating 20% of a cohort of 1 million 50 year old individuals at the age of 60 years, approximately 20,000 HZ-cases will be avoided over life-time. The NNV to avoid one HZ (PHN)-case was 10 (144). However, with a BCR of 0.34 this vaccination-strategy did not save costs. The base-case-analysis yielded an ICER of 1,419 (20,809) Euros per avoided HZ (PHN)-case and 28,146 Euros per QALY gained. Vaccination at the age of 60 was identified in most (sensitivity) analyses to be the most cost-effective vaccination strategy. In DSA, vaccine price and VE were shown to be the most critical input-data. Conclusions According to our evaluation, HZ-vaccination is expected to avoid HZ/PHN-cases and gain QALYs to higher costs. However, the vaccine price had the highest impact on the ICERs. Among different scenarios, targeting individuals aged 60 years seems to represent the most cost-effective vaccination-strategy.